Indications and outcome of patients undergoing cutaneous ureterostomy as a mode of urinary diversion after radical cystectomy: an experience from a tertiary care center - Agarwal, Shikhar; Sarpal, Rajeev; Dang, Shivam; Kalra, Yogesh; Biswas, Manoj (International Surgery Journal, 2018)
Background: Radical cystectomy is associated with high morbidity, especially in elderly patients. Most of the associated complications are related to the urinary diversion. Cutaneous ureterostomy (CU) is usually an uncommon form of urinary diversion and is avoided because of the frequent complication of stomal stenosis. Methods: In this study the authors retrospectively analyzed 84 patients who underwent radical cystectomy. 17 Patients who underwent single stoma CU were included in the study who required lifelong monthly stent changes. Varied indication and outcome of these patients were analyzed. Results: Patients in which CU was used as a mode of urinary diversion had less blood loss, less operative time and discharged without ICU stay. Conclusions: It seems that single stoma CU is a viable option in elderly, high risk patients and in post radiotherapy patients who require radical cystectomy. Although the patient requires lifelong stent changes, postoperative complications are reduced.